Pharmaceutical and pharmacological studies of Shen Ma Yi Zhi granule for prevention of vascular dementia: A review - Chang, Su-rui; Liu, Jian-gang; Li, Hao; Liu, Mei-xia; Shi, Dan-dan; Zhou, Li-juan (Frontiers in Neuroscience, 2022)
Background: As dementia leads to hospitalization and disability mainly in elderly people, the whole society is facing challenge of withstanding the growing burdens of elderly supporting. Majority of patients in the elderly with cognitive disorder have a vascular component that is identifiable and preventable and treatable by several methods. That calls for more attention on further studying of dementia curing and preventing. Compounds of Traditional Chinese Medicine show the advantages of multi-targets of improving cognitive and protecting neuron et al. Shen Ma Yi Zhi Granule is one compound that has been clinically proved effective. Pharmaco-mechanism, pharmacokinetics and clinical applications of SMYZG various animal models and the patho-physiological characters of VaD have been conducted with proper methods. SMYZG can active and regulate four main signal pathways related to VaD, including AMPK / PPARα / PGC-1α / UCP2 pathway, Nrf2 / HO-1 pathway, HIF-1 / VEGF / Notch pathway, VEGF ／ Flk-1 ／ p8 MAPK pathway. SMYZG can effect on anti-inflammatory and anti-oxidant stress response, can repair demyelination of brain white matters and vascular endothelium, can regulate pericytes and mitochondrial energy metabolism. SMYZG exerts a protective effect against neuron injury and vessel endothelium regeneration and improve study and cognitive functions in rats with VaD. SMYZG has high value of further research and development.